2013
DOI: 10.1161/atvbaha.112.300128
|View full text |Cite
|
Sign up to set email alerts
|

Role of Extracellular Vesicles in De Novo Mineralization

Abstract: Extracellular vesicles are membrane micro/nanovesicles secreted by many cell types into the circulation and the extracellular milieu in physiological and pathological conditions. Evidence suggests that extracellular vesicles, known as matrix vesicles, play a role in the mineralization of skeletal tissue, but emerging ultrastructural and in vitro studies have demonstrated their contribution to cardiovascular calcification as well. Cells involved in the progression of cardiovascular calcification release active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 55 publications
2
70
0
2
Order By: Relevance
“…Similar patterns have been described both in clinical studies [14] and in in vitro studies [24]. However, some researchers state that dynamic stress promotes the development of calcification, but it is not its primary cause [13].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Similar patterns have been described both in clinical studies [14] and in in vitro studies [24]. However, some researchers state that dynamic stress promotes the development of calcification, but it is not its primary cause [13].…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies have shown that cardiovascular calcification is triggered through the activation of cellular processes in the presence of an uncontrolled pathological environment that cannot be reproduced in the in vitro models. Therefore, it limits the opportunities to investigate the cause-effect relationships, mostly studied by the endpoints of the affected tissues [14,15]. Smooth muscle cells are considered to be the main source of origin of osteogenic cells in calcified vascular lesions [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They contain the same enzymes such as tissue nonspecific alkaline phosphatase which are critical in altering the local microenvironment to precipitate ectopic calcification (75). These pathological MV are also dependent on annexins II, V, and VI for mineral deposition identical to MV from normal osteoblasts and chondrocytes (12).…”
Section: Emerging Concepts In Vascular Calcificationmentioning
confidence: 99%